The MST and land reform of consensus - Santos, Arlete Ramos dos (FCL-UNESP Laboratório Editorial, 2017)
This text puts forth the results of research undertaken in the Far South of Bahia, which analyzed the partnerships, agreements and dialogue established between social movements of the country, mainly the Landless Movement, the State and agribusiness companies. We used exploratory qualitative methodology to analyze data collected through review of documentation and semi-structured interviews. The results show that in the Brazilian region studied, a new agrarian reform is taking place, which we’re styling Consensus Agrarian Reform.